REGULATING BANKS - WHITWORTH, ANDREW (AGENDA PUBLISHING, 2021)
Far from creating stability, argues Andrew Whitworth, the regulatory impulse of policy-makers since the financial crisis has inevitably led to greater instability in the banking sector and fails to avoid future boom and bust cycles.